PENGARUH PENYULUHAN TENTANG REPRODUKSI REMAJA TERHADAP PENGETAHUAN DAN SIKAPPADASISWA/ISMPMUHAMMADIYAH 61TJ SELAMAT - Dinda Sari Apriliani; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
In adolescence there are many changes and problems, which if not dealt with quickly will become a prolonged problem and have a serious impact. Promotion of reproductive health in adolescents is often connoted as sex education where most Indonesian people still taboo this. Even in formal education institutions at the secondary school level, they are still hesitant to carry out reproductive health counseling to their students. Meanwhile, adolescence is a phase of growth and development when individuals reach the age of 10-19 years. the low knowledge of adolescents about adolescent reproductive health will affect the attitude that will be carried out by adolescents related to adolescent reproductive health. The purpose of this study was to describe the level of knowledge and attitudes about reproductive health among students at SMP Muhammadiyah 61 Tanjung Selamat. This type of research is an experimental research using pretest and posttest (one group pretest and posttest design). The research subjects were 60 students of grade VII SMP Muhammadiyah 61 Tanjung Selamat, 40 respondents were female, 20 respondents were male, of which 51 respondents were 12 years old, 9 respondents were 13 years old. In this study, based on the test analysis that had been carried out, there was an effect of adolescent reproductive health counseling on the knowledge and attitudes of respondents after the intervention was carried out. The conclusion of this study is the lack of knowledge of adolescents on reproductive health. So it should be held more often reproductive health counseling on adolescents.